Evening melatonin in January after changes in hours of habitual exercise during fall among youths living in the subarctic. - Weydahl, Andi (Nordic Council for Arctic Medical Research, 1994)
Secretion of the hormone melatonin shows a circadian rhythm and is inhibited by light. Light therapy with phase shifting of the melatonin rhythm has been used as treatment of sleeping problems and seasonal affective disorders (SAD). Exercise has also been shown to suppress the melatonin secretion. In order to investigate the effect of increased level of habitual physical activity upon melatonin secretion in areas with extreme short days and high level of midwinter insomnia, 18 high school students participated in this study. Their habitual physical activity throughout two consecutive falls were recorded. The following January, blood samples were taken for melatonin analyses from 1530h to 2300h. After the fall with highest habitual activity level, the plasma melatonin showed significantly decreased values at all sampling times compared to values after lowest level of activity. The relative increase in melatonin level at 2300h, however, tended to be of a greater magnitude after the fall with highest activity cornpared to the fall with Iowest activity (p=.094). A change in habitual level of activity should be thought of as a possible help for treating midwinter insomnia and SAD.